2014
DOI: 10.1111/ijsw.12098
|View full text |Cite
|
Sign up to set email alerts
|

European worlds of inclusive activation: The organisational challenges of coordinated service provision

Abstract: For activation policies to succeed, the provision of social services in addition to labour‐market services is essential, as social services are a prerequisite for integrating groups with complex social problems into the labour market. Activation policies based on social services can be termed inclusive. They require not only a sufficient financial basis, but also governance structures that deal with the organisational challenges associated with coordinated service provision, including fragmented competences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 35 publications
0
56
0
3
Order By: Relevance
“…Many shadow programmes exist, showing no clear outputs, let alone evidence of impact. This fragmentation of services stands in contrast to growing international calls for the integration of ALMPs into other social services (Minas, ); and for the implementation of principles of New Public Management of performance measurement, competition benchmarking, auditing and one‐stop‐shops in service delivery (Heidenreich & Aurich‐Beerheide, ).…”
Section: Conclusion and Strategies For Reformmentioning
confidence: 99%
See 1 more Smart Citation
“…Many shadow programmes exist, showing no clear outputs, let alone evidence of impact. This fragmentation of services stands in contrast to growing international calls for the integration of ALMPs into other social services (Minas, ); and for the implementation of principles of New Public Management of performance measurement, competition benchmarking, auditing and one‐stop‐shops in service delivery (Heidenreich & Aurich‐Beerheide, ).…”
Section: Conclusion and Strategies For Reformmentioning
confidence: 99%
“…Second, the analysis contributes to the theorisation about ALMPs in welfare regimes in developing countries. This is an exercise fraught with theoretical challenges, in that ALMPs have primarily been studied in the context of welfare regimes in developed countries (see e.g., Bonoli, ; Heidenreich & Aurich‐Beerheide, ; Lindsay & Mailand, ). Studying ALMPs outside this context is curtailed by the dual challenge of the weak state of knowledge and a tenuous theoretical backing.…”
Section: Introductionmentioning
confidence: 99%
“…Bentolila et al (2012) have highlighted the importance of the difference between the EPL for fixed-term and permanent contracts, because larger gaps between dismissal costs for permanent and temporary jobs might increase the unemployment risks especially for temporary workers. This refers to the role of activation strategies, which may increase the obligation, possibility and interest in taking up a new job through various enabling and demanding measures (Heidenreich and Aurich-Beerheide, 2014). A higher EPL level should be correlated with higher unemployment while a higher gap should lower the risk of LTU for persons with a fixed-term contract, because firing costs are lower (Boeri, 2011).…”
Section: Institutional Occupational and Individual Determinants Of Smentioning
confidence: 99%
“…Heidenreich and Aurich‐Beerheide's () description of a necessary twofold services provision in frontline work is reflected in Frøyland and Spjelkavik's (2012) and Spjelkavik's () twofold definition of activation competency. They suggested that activation competency consists of two distinct dimensions: labour market competency and user‐oriented competency.…”
Section: Introductionmentioning
confidence: 99%